Sovietization of Lithuania and Appropriation of Jewish Cultural Heritage (Based on the Documents in Lithuanian Central State Archive) - Lempert, Lara (Literatūra, 2025)
The article presents and discusses a sample of documents dating back to the period of the first Soviet occupation of Lithuania (1940) from the Lithuanian Central State Archives, pertaining to juridical and/or actual liquidation of the Vilna Jewish community and its key cultural institutions: the Mattityahu Strashun and Mefitse Нaskala libraries and the museum of An-sky Historical and Ethnographical Society. The documents testify to the loss of institutional identity and status, and gradual absorbing of these institutions into ideologically acceptable ones, which was going on until the Nazi occupation of Lithuania. Paradoxically enough, it was the bureaucratic accuracy of the Soviets that, in the course of nationalization, created an overview of these institutions and their collections, thereby providing the last glimpse of the pre-Holocaust state of several key Vilnius Jewish institutions and their collections, later plundered by the Nazis who annihilated the majority of the Jewish population of Vilnius and destroyed the community and its culture. In the appendix of the article, several unpublished documents and their fragments are presented from the period discussed in the article.